A Delphi investigation into the corporate governance practices of Albanian joint stock companies - Çipi, A.; Llaci, S.; Ferreira, F. (International Journal of Transitions and Innovation Systems, 2014)
A 'good' corporate governance (CG) framework should protect shareholders' rights and ensure their equitable treatment, including minorities and foreign shareholders. It should also encourage active cooperation between corporations and stakeholders in creating wealth-generating economic conditions. In this sense, few would contest that 'good' CG practices boost the attraction of powerful foreign investors. Due to the importance that foreign investors have in developing countries, such as Albania, one may assume that the implementation of CG mechanisms in such places is beneficial for companies and the countries' economy. This paper aims to analyse the current situation of CG practices in Albania, based on an application of the Delphi technique to a panel of Albanian chief executive officers (CEOs). Despite the short life of joint stock companies (JSC) in the Albanian trade market, results show that CEOs have a good level of knowledge regarding the basic mechanisms of CG. There is still room, however, for improvements in the implementation of these mechanisms and in the adoption of the internationally accepted CG best practices.